Effectiveness of Green Trust as a Mediating Variable in Extending TPB Theory to Electrical Automotive Adoption in Indonesia - Abi Yusuf Nur Asida; Rini Kuswati; Muhammad Sholahuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the effectiveness of Green Trust as a mediating variable in expanding the TPB theory for the adoption of electric vehicles in Indonesia. The study method used is a quantitative method. Sampling in this study used a non-probability sampling technique with a purposive sampling method, where researchers deliberately selected respondents who were considered relevant for research purposes. Data was collected through questionnaires to all Indonesian people who have the intention to adopt automotive electrical. The data collection process was carried out through the use of a questionnaire with a Likert scale. The total number of respondents involved in this study was 425 respondents. The data analysis technique used in this study is the SEM PLS method, which consists of outer model and inner model analysis, with the help of SMARTPLS 4.0 software. The research results show that extensions of the TPB theory such as Attitude, Subjective Norm, and PBC variables have an effect on electrical automotive adoption, but green trust does not mediate the relationship between attitude and subjective norm towards adoption (EAV). This research provides valuable recommendations to increase the widespread adoption of electric automobiles in Indonesia.